WORLD OF HESIOD - Burn, A. R. (Andrew Robert), 1902-1991. Link ([S.l.])
1 online resource
Keywords: The World of Hesiod (1936) examines the world of the Ancient Greeks before Ionian rationalism and the civilisation of Athens. Lying between the Heroic Age and the Lyric Age, Hesiod and the Geometric potters and painters set the scene for the economic, political and social changes that were to follow.